Pengembangan Pembelajaran Interaktif Sejarah Proklamasi Berbasis Game Mobile 2D Menggunakan Metode Game Development Life Cycle - Habil Jabbal Firdausyi; Ade Irma Purnamasari; Irfan Ali; Indra Wiguna Marthanu; Fathurrohman Fathurrohman (Yayasan Kawanad, 2026)
The History subject — particularly the Indonesian Proclamation of Independence — has long been delivered through conventional, one-directional methods that leave students disengaged and, in documented cases, visibly saturated. This study designed and developed an interactive digital learning medium as a direct response to that condition. The medium produced is a narrative-driven 2D Mobile Game, built using the Game Development Life Cycle (GDLC) across four phases: Concept, Pre-Production, Production, and Testing. The resulting prototype centers on a slide-controlling mechanism and a sequentially structured historical narrative, with an integrated quiz system embedded at the end of each story chapter. Validation by a Material Expert and a Media/Technology Expert placed the product in the